Evolution of DNA Amounts Across Land Plants (Embryophyta) - LEITCH, I. J. (Ann Bot, 2005)
• Background and Aims DNA C-values in land plants (comprising bryophytes, lycophytes, monilophytes, gymnosperms and angiosperms) vary ∼1000-fold from approx. 0·11 to 127·4 pg. To understand the evolutionary significance of this huge variation it is essential to evaluate the phylogenetic component. Recent increases in C-value data (e.g. Plant DNA C-values database; release 2.0, January 2003; http://www.rbgkew.org.uk/cval/homepage.html) together with improved consensus of relationships between and within land plant groups makes such an analysis timely. • Methods Insights into the distribution of C-values in each group of land plants were gained by superimposing available C-value data (4119 angiosperms, 181 gymnosperms, 63 monilophytes, 4 lycophytes and 171 bryophytes) onto phylogenetic trees. To enable ancestral C-values to be reconstructed for clades within land plants, character-state mapping with parsimony and MacClade was also applied. • Key Results and Conclusions Different land plant groups are characterized by different C-value profiles, distribution of C-values and ancestral C-values. For example, the large (∼1000-fold) range yet strongly skewed distribution of C-values in angiosperms contrasts with the very narrow 12-fold range in bryophytes. Further, character-state mapping showed that the ancestral genome sizes of both angiosperms and bryophytes were reconstructed as very small (i.e. ≤1·4 pg) whereas gymnosperms and most branches of monilophytes were reconstructed with intermediate C-values (i.e. >3·5, <14·0 pg). More in-depth analyses provided evidence for several independent increases and decreases in C-values; for example, decreases in Gnetaceae (Gymnosperms) and heterosperous water ferns (monilophytes); increases in Santalales and some monocots (both angiosperms), Pinaceae, Sciadopityaceae and Cephalotaxaceae (Gymnosperms) and possibly in the Psilotaceae + Ophioglossaceae clade (monilophytes). Thus, in agreement with several focused studies within angiosperm families and genera showing that C-values may both increase and decrease, it is apparent that this dynamic pattern of genome size evolution is repeated on a broad scale across land plants.